Investigation of Ionospheric Small‐Scale Plasma Structures Associated With Particle Precipitation - F. Enengl; L. Spogli; D. Kotova; Y. Jin; K. Oksavik; N. Partamies; W. J. Miloch (Space Weather)
Abstract We investigate the role of auroral particle precipitation in small‐scale (below hundreds of meters) plasma structuring in the auroral ionosphere over the Arctic. In this scope, we analyze together data recorded by an Ionospheric Scintillation Monitor Receiver (ISMR) of Global Navigation Satellite System (GNSS) signals and by an All‐Sky Imager located in Longyearbyen, Svalbard (Norway). We leverage on the raw GNSS samples provided at 50 Hz by the ISMR to evaluate amplitude and phase scintillation indices at 1 s time resolution and the Ionosphere‐Free Linear Combination at 20 ms time resolution. The simultaneous use of the 1 s GNSS‐based scintillation indices allows identifying the scale size of the irregularities involved in plasma structuring in the range of small (up to few hundreds of meters) and medium‐scale size ranges (up to few kilometers) for GNSS frequencies and observational geometry. Additionally, they allow identifying the diffractive and refractive nature of fluctuations on the recorded GNSS signals. Six strong auroral events and their effects on plasma structuring are studied. Plasma structuring down to scales of hundreds of meters is seen when strong gradients in auroral emissions at 557.7 nm cross the line of sight between the GNSS satellite and receiver. Local magnetic field measurements confirm small‐scale structuring processes coinciding with intensification of ionospheric currents. Since 557.7 nm emissions primarily originate from the ionospheric E‐region, plasma instabilities from particle precipitation at E‐region altitudes are considered to be responsible for the signatures of small‐scale plasma structuring highlighted in the GNSS scintillation data.